Shifts in High Arctic tundra vegetation structure linked to variation in soil conditions - Jana Ruethers; Lena Bakker; Sebastian Doetterl; Simone Fior; Jamila Gisler; Cara Magnabosco; Annina Maier; Moritz Mainka; Kristine Bakke Westergaard; Jake Alexander (Polar Biology, 2026)

Genomic Signatures of Adaptation Across a Precipitation Gradient From Niche Centre to Niche Edge - Samantha Van Deurs; Oliver Reutimann; Hirzi Luqman; Dikla Lifshitz; Einav Mayzlish‐Gati; Jake Alexander; Simone Fior (Molecular Ecology, 2025)
Evaluating the potential for species to adapt to changing climates relies on understanding current patterns of adaptive variation and selection, which might vary in intensity across a species' niche, hence affecting our inference of where adaptation might be most important in the future. Here, we investigate the genetic basis of adaptation in Lactuca serriola along a steep precipitation gradient in Israel approaching the species' arid niche limit and use candidate loci to inform predictions of its past and future adaptive evolution. Environmental association analyses combined with generalised dissimilarity models revealed 108 candidate genes showing nonlinear shifts in allele frequencies across the gradient, with 66% of these genes under strong selection near the dry niche edge. We detected selection acting on genes with separate suites of biological functions, specifically related to phenology and responses to environmental stressors, including osmotic stress, at the dry niche edge, and related to biotic interactions and defence closer to the niche centre. The adaptive genetic composition of populations, as inferred through polygenic risk scores, point to intensified selection operating towards the dry niche edge. However, inference of past and future evolutionary change predicts larger adaptive shifts occurring in the mesic part of the range, which is most affected by climate change. Our study reveals that adaptive shifts in response to climate change can be heterogeneous across a species' range and not necessarily strongest near its niche edge.

Polygenic routes lead to parallel altitudinal adaptation in Heliosperma pusillum (Caryophyllaceae) - Aglaia Szukala; Jessica Lovegrove‐Walsh; Hirzi Luqman; Simone Fior; Thomas M. Wolfe; Božo Frajman; Peter Schönswetter; Ovidiu Paun (Molecular Ecology, 2023)
Understanding how organisms adapt to the environment is a major goal of modern biology. Parallel evolution—the independent evolution of similar phenotypes in different populations—provides a powerful framework to investigate the evolutionary potential of populations, the constraints of evolution, its repeatability and therefore its predictability. Here, we quantified the degree of gene expression and functional parallelism across replicated ecotype formation in Heliosperma pusillum (Caryophyllaceae), and gained insights into the architecture of adaptive traits. Population structure analyses and demographic modelling support a previously formulated hypothesis of parallel polytopic divergence of montane and alpine ecotypes. We detect a large proportion of differentially expressed genes (DEGs) underlying divergence within each replicate ecotype pair, with a strikingly low number of shared DEGs across pairs. Functional enrichment of DEGs reveals that the traits affected by significant expression divergence are largely consistent across ecotype pairs, in strong contrast to the nonshared genetic basis. The remarkable redundancy of differential gene expression indicates a polygenic architecture for the diverged adaptive traits. We conclude that polygenic traits appear key to opening multiple routes for adaptation, widening the adaptive potential of organisms.

Population genomic evidence for plant glacial survival in Scandinavia - Kristine B. Westergaard; Niklaus Zemp; Leo P. Bruederle; Hans K. Stenøien; Alex Widmer; Simone Fior (Molecular Ecology, 2019)
Quaternary glaciations have played a major role in shaping the genetic diversity and distribution of plant species. Strong palaeoecological and genetic evidence supports a postglacial recolonization of most plant species to northern Europe from southern, eastern and even western glacial refugia. Although highly controversial, the existence of small in situ glacial refugia in northern Europe has recently gained molecular support. We used genomic analyses to examine the phylogeography of a species that is critical in this debate. Carex scirpoidea Michx subsp. scirpoidea is a dioecious, amphi‐Atlantic arctic–alpine sedge that is widely distributed in North America, but absent from most of Eurasia, apart from three extremely disjunct populations in Norway, all well within the limits of the Weichselian ice sheet. Range‐wide population sampling and variation at 5,307 single nucleotide polymorphisms show that the three Norwegian populations comprise unique evolutionary lineages divergent from Greenland with high between‐population divergence. The Norwegian populations have low within‐population genetic diversity consistent with having experienced genetic bottlenecks in glacial refugia, and host private alleles that probably accumulated in long‐term isolated populations. Demographic analyses support a single, pre‐Weichselian colonization into Norway from East Greenland, and subsequent divergence of the three populations in separate refugia. Other refugial areas are identified in North‐east Greenland, Minnesota/Michigan, Colorado and Alaska. Admixed populations in British Columbia and West Greenland indicate postglacial contact. Taken together, evidence from this study strongly indicates in situ glacial survival in Scandinavia.

The genomic basis of adaptation to calcareous and siliceous soils in Arabidopsis lyrata - Alessia Guggisberg; Xuanyu Liu; Léonie Suter; Guilhem Mansion; Martin C. Fischer; Simone Fior; Marie Roumet; Ruben Kretzschmar; Marcus A. Koch; Alex Widmer (Molecular Ecology, 2018)
Edaphic conditions are important determinants of plant fitness. While much has been learnt in recent years about plant adaptation to heavy metal contaminated soils, the genomic basis underlying adaptation to calcareous and siliceous substrates remains largely unknown. We performed a reciprocal germination experiment and whole‐genome resequencing in natural calcareous and siliceous populations of diploid Arabidopsis lyrata to test for edaphic adaptation and detect signatures of selection at loci associated with soil‐mediated divergence. In parallel, genome scans on respective diploid ecotypes from the Arabidopsis arenosa species complex were undertaken, to search for shared patterns of adaptive genetic divergence. Soil ecotypes of A. lyrata display significant genotype‐by‐treatment responses for seed germination. Sequence (SNPs) and copy‐number variants (CNVs) point towards loci involved in ion transport as the main targets of adaptive genetic divergence. Two genes exhibiting high differentiation among soil types in A. lyrata further share trans‐specific single nucleotide polymorphisms with A. arenosa . This work applies experimental and genomic approaches to study edaphic adaptation in A. lyrata and suggests that physiological response to elemental toxicity and deficiency underlies the evolution of calcareous and siliceous ecotypes. The discovery of shared adaptive variation between sister species indicates that ancient polymorphisms contribute to adaptive evolution.

Genomewide signatures of selection in Epichloë reveal candidate genes for host specialization - Melanie K. Schirrmann; Stefan Zoller; Daniel Croll; Eva H. Stukenbrock; Adrian Leuchtmann; Simone Fior (Molecular Ecology, 2018)
Host specialization is a key process in ecological divergence and speciation of plant‐associated fungi. The underlying determinants of host specialization are generally poorly understood, especially in endophytes, which constitute one of the most abundant components of the plant microbiome. We addressed the genetic basis of host specialization in two sympatric subspecies of grass‐endophytic fungi from the Epichloë typhina complex: subsp. typhina and clarkii . The life cycle of these fungi entails unrestricted dispersal of gametes and sexual reproduction before infection of a new host, implying that the host imposes a selective barrier on viability of the progeny. We aimed to detect genes under divergent selection between subspecies, experiencing restricted gene flow due to adaptation to different hosts. Using pooled whole‐genome sequencing data, we combined F ST and D XY population statistics in genome scans and detected 57 outlier genes showing strong differentiation between the two subspecies. Genomewide analyses of nucleotide diversity (π), Tajima's D and d N / d S ratios indicated that these genes have evolved under positive selection. Genes encoding secreted proteins were enriched among the genes showing evidence of positive selection, suggesting that molecular plant–fungus interactions are strong drivers of endophyte divergence. We focused on five genes encoding secreted proteins, which were further sequenced in 28 additional isolates collected across Europe to assess genetic variation in a larger sample size. Signature of positive selection in these isolates and putative identification of pathogenic function supports our findings that these genes represent strong candidates for host specialization determinants in Epichloë endophytes. Our results highlight the role of secreted proteins as key determinants of host specialization.

Anisocotyly and meristem initiation in an unorthodox plant, Streptocarpus rexii (Gesneriaceae) - Raffaella Mantegazza; Michael Möller; C. Jill Harrison; Simone Fior; Chiara De Luca; Alberto Spada (Planta, 2007)